If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 7 = 2x + -5 Reorder the terms: 7 + 3y = 2x + -5 Reorder the terms: 7 + 3y = -5 + 2x Solving 7 + 3y = -5 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3y = -5 + -7 + 2x Combine like terms: 7 + -7 = 0 0 + 3y = -5 + -7 + 2x 3y = -5 + -7 + 2x Combine like terms: -5 + -7 = -12 3y = -12 + 2x Divide each side by '3'. y = -4 + 0.6666666667x Simplifying y = -4 + 0.6666666667x
| N/10-20=20 | | 100x-40y=320 | | 6x7/8= | | 3z+5z=0.6 | | (n)(n)+72=-17n | | 3x-5=6+x | | 6x+7=3(2x+4) | | (k)(k)-11k+30=0 | | (12y)(12y)+40y=7 | | 3x^2-8+5x=0 | | 3x+6=507 | | 10/3x1/2 | | 6d+4=-32 | | 5/6z=5/7 | | 18/sin40 | | a=bd | | p^2-14p=51 | | (d)(d)=5d | | 10c/2-32/4=56/8 | | (w)(w)=12 | | 3/7x1/7 | | 6-9(1-7n)=-21 | | -4x-16y=-12 | | 2y=-5x-3 | | (2x+8)+(3x-4)+x= | | 8(x+9)=72 | | 3y-10+y+y-10=180 | | (3b)(3b)+7b-6=0 | | x=(2x+8)+(3x-4)-x | | m(m-3)-2m(m-4)=-(m^2-4m)6 | | x^2-12=36-2x^2 | | -12+4x=12 |